Influence of celebrity endorsement on purchase intention toward smartphones among Gen Y / Rusydee Aqim Roslam - Roslam, Rusydee Aqim (Faculty of Business and Management, 2018)
The practice of celebrity endorsement has become an effective marketing tool for companies to communicate about their products to the consumers in recent years. The purpose of this study is to investigate the influence of celebrity endorsement on customer purchase intention in smartphone industry. Celebrity attractiveness, celebrity expertise, celebrity trustworthiness and celebrity congruence are the characteristics of celebrity endorsement used in this study. This study is conducted among Gen Y in Bandaraya Melaka by using convenience sampling. Data were collected from 110 respondents by using structured questionnaire and the results were analysed by using SPSS 20. The results indicated that celebrity attractiveness, celebrity expertise, celebrity trustworthiness and celebrity congruence have positive relationship with purchase intention. The result also shows that celebrity trustworthiness has the strongest impact on purchase intention. Based on these results, several recommendations have been made for smartphone companies and also for future research purposes.